Tipe Magmatik Batuan Beku Formasi Gabon di Tinggian Karangbolong, Kebumen - Chusni Ansori; Fitriany A Wardhani (Jurnal Geologi dan Sumberdaya Mineral, 2019)
Karangbolong High located in Java Southern Mountain range is dominated by volcanic rocks of Gabon Formation in the form of volcanic breccia, some intrusion bodies and lavas. Research on the type of magma at Karangbolong high has never been done. This activity is intended to know the distribution, change the type of magma and tectonic position.This research includes field sampling and laboratory work which includes petrographic analysis using polarization microscope and geochemistry analysis 4 litho ICP-WRA for major element and ICP-WRA4B2 for trace elements and REE. Results of geochemistry analysis are.plot in Total Alkali Silica (TAS) diagrams, AFM diagram , SiO2 vs FeO(t) / MgO diagram, SiO2 Vs K2O and the spider diagram.for trace elements and REE.Most of the igneous rocks at Karangbolong Region are andesite pyroxene, basaltic andesite and slightly basalt olivine. To the northward, igneous rocks are tend to more acid as reflected by the increase of SiO2, Na2O and K2O and the decreasing of MgO and Fe2O3 content. The affinity of the magma in the northern part is mostly Calc-Alkaline series (KR-18, KR-28, KR-6, KR-23) and slightly Island Arc Tholeiite as intrusion and lava at southern part (KR-33 and KR- 17). The tectonic position of rock formation resides in Island Arc Plate Margin. The Calk-alkaline magma is enriched with the light rare earth elements (LREE) compared to the Tholeiite magma, while trace element Sr, K, Rb, Ba, and Th strongly enriched in.Keywords : Karangbolong High, igneous rock, magmatic type, tectonic position